Social sciences and the government : the Asian scene - Narain, Iqbal; Atal, Yogesh; Association of Asian Social Science Research Councils (New Delhi : Lancer International in association with the Association of Asian Social Science Research Councils, 1987)
Contributed papers from social science research councils of eleven Asian countries.
Includes bibliographies.
Koleksi Sumbangan : Dr. Syed Husin Ali.
Keywords: Social sciences and state -- Asia